The Archipelago's Development of Career Meaning Background: An Analysis of Bangka Belitung's Career Counseling Services - Nikmarijal; Sandri; Jordi; Atika Delvani Rafi; Wilda Rahma; Helya Arnani (Sustainable, 2025)
Bangka Belitung through the perspective of career counseling services. A qualitative approach using Interpretative Phenomenological Analysis (IPA) was employed. Participants were senior high school students purposively selected based on their involvement in career counseling services. Data were collected through in-depth interviews, limited observations, and document analysis, and analyzed using interpretative thematic analysis. The findings indicate that career meaning is constructed through a negotiation process involving personal aspirations, family influence, local cultural values, and structural constraints of the island context. Career is predominantly understood as a means of life security and social sustainability rather than self-actualization. The study also reveals a tension between globally shaped career aspirations and locally constrained realities. Career counseling services are perceived primarily as sources of information rather than reflective spaces that facilitate contextual career meaning-making. This study highlights the need for more contextual, reflective, and dialogical career counseling practices to better align with students’ socio-cultural realities in island regions.